Scientific rigour of online platforms for 3D visualization of heritage - Nataska Statham (Virtual Archaeology Review)
3D visualisations –including 3D scans and 3D reconstructions–designed as part of larger archaeology, history or cultural heritage  projects  are  commonly  shared  with  the  public  through  online  platforms  that  were  not  necessarily  designed  to host  heritage  representations  and  often  fail  to  contextualize  them.  This  paper  seeks  to  evaluate  whether five online platforms commonly used today to share 3D visualisations of heritage (Google Arts & Culture, CyArk, 3DHOP, Sketchfab and  game  engines) offer  features that  facilitate  their scientific  rigour and community  participation,  based  on guidelines from International Council on Monuments and Sites(ICOMOS)and United Nations Educational, Scientific, and Cultural Organization(UNESCO). The author starts by summarizing recommendations from 32 international guidelines that are relevant to the 3D visualization of heritage, condensing them into nine key criteria: multi-disciplinary teams, objective-driven  methodology  and  tools,  careful  documentation, type  of  reconstruction  and  level  of  certainty,  authenticity, alternative  hypotheses,  multiple  historical  periods,  respectful  use  of  the  heritage, and  community  engagement. The author proceeds to review the platforms above comparing their features with these nine recommendations and concludes that, while there are currently available features that could help to elevate the scientific rigour of the 3D visualisations and their contextualization to  the  public, they are  not  mandatory  and  are  seldom  used.  The  paper  finishes  with  a recommendation for an information package to support3D visualisations of heritage on public online platforms.